Politics of the womb : women, reproduction, and the state in Kenya - Thomas, Lynn M. (ACLS Fellows' publications., 2003)
In more than a metaphorical sense, the womb has proven to be an important site of political struggle in and about Africa. By examining the political significance--and complex ramifications--of reproductive controversies in twentieth-century Kenya, this book explores why and how control of female initiation, abortion, childbirth, and premarital pregnancy have been crucial to the exercise of colonial and postcolonial power.